Risk factors for anaemia among women and their young children hospitalised with suspected thiamine deficiency in northern Lao PDR - Sonja Y. Hess; Taryn J. Smith; Dalaphone Sitthideth; Charles D. Arnold; Xiuping Tan; Kerry S. Jones; Kenneth H. Brown; Silvia Alayon; Sengchanh Kounnavong (Wiley, 2024)
Abstract Anaemia among women and young children remains a major public health concern. This secondary study describes the anaemia prevalence among young hospitalised children and their mothers in northern Lao People's Democratic Republic and explores possible nutritional causes and risk factors for anaemia. Hospitalised children (ages 21 days to <18 months) with clinical symptoms suggestive of thiamine deficiency disorders were eligible along with their mothers. Venous blood was collected for determination of haemoglobin, ferritin, soluble transferrin receptor (sTfR), retinol‐binding protein (RBP), erythrocyte glutathione reductase activation coefficient (EGRac), thiamine diphosphate (ThDP) and acute phase proteins. Risk factors for anaemia were modelled using minimally adjusted logistic regression controlling for age. Haemoglobin results were available for 436 women (mean ± SD age 24.7 ± 6.4 years; 1.6% pregnant) and 427 children (4.3 ± 3.5 months; 60.3% male). Anaemia prevalence (Hb < 120 g/L for nonpregnant women and <110 g/L for pregnant women and children) was 30.7% among women and 55.2% among children. In bivariate analyses, biomarkers significantly associated with anaemia in women were ferritin, sTfR, RBP, EGRac and ThDP. Other risk factors for women were lower BMI, mid‐upper arm circumference < 23.5 cm, lower education, lower socioeconomic index, food insecurity, Hmong ethnicity, not/rarely having attended antenatal care, not having taken antenatal iron‐containing supplements and not meeting minimum dietary diversity. Risk factors for anaemia among children were older age, male sex, stunting, sTfR, ThDP and alpha‐1‐acid‐glycoprotein. Anaemia was common among women and their hospitalised children and was associated with micronutrient deficiencies and socioeconomic, dietary and health care‐seeking risk factors, suggesting that multiple strategies are required to prevent anaemia among women and children.